HUBUNGAN ANTARA XEROSTOMIA DENGAN GENDER DAN USIA PADA KELOMPOK LANJUT USIA DI KOTA DUMAI - bakar, abu; Ningrum, Valendriyani (Universitas Baiturrahmah, 2023)
Introduction: The elderly population is increasing both globally and nationally, including in Dumai City, Riau Province. The older they get, the more health problems they complain about, and xerostomia is one of the most common issues. There are only a few studies that examine the problem of xerostomia in the elderly. Therefore, the purpose of this study is to examine how xerostomia relates to gender, age, and overall health among elderly people in Dumai City, Riau Province. Methods: This study used a cross-sectional design approach. The survey included data on gender, age, and subjective assessment of xerostomia using the Summated Xerostomia Inventory in Indonesian (SXI-ID) questionnaire, consisting of 5 questions with answer options: never, rarely, sometimes, often, and always. In addition, the standard xerostomia question,